Enhancing Math Skills in Children with Learning Difficulties Using Smartphone Apps - Ali A. Al-Barakat; Rommel M. AlAli; Omayya M. Al-Hassan; Bushra A. Alakashee; Yusra Z. Aboud; Ali K. Abdullatif (Emerging Science Journal, 2025)
This study aimed to examine the effectiveness of smartphone applications in enhancing the acquisition of mathematical concepts among children with learning difficulties. The research involved 80 students from private schools in northern Jordan, randomly assigned to an experimental group, which received instruction through smartphone and tablet applications, and a control group, which followed conventional teaching methods. Pre- and post-intervention cognitive assessments were conducted over a 12-week instructional period to measure mathematical understanding. The results revealed that students in the experimental group showed a significant improvement in mathematical performance compared to the control group. Furthermore, no statistically significant differences were found between male and female students, and no interaction effect between gender and instructional method was observed, indicating equitable outcomes across genders. The study highlights that smartphone-based educational applications provide an interactive, adaptive, and supportive learning environment that caters to the specific needs of students with learning difficulties. The novelty of this research lies in demonstrating the practical benefits of integrating digital tools into mathematics instruction, supporting constructivist and inclusive learning approaches, and offering evidence-based strategies to enhance student engagement and conceptual understanding. These findings suggest that technology-enhanced learning can effectively supplement traditional methods, promoting improved academic performance and inclusive educational practices.